2019
DOI: 10.3390/w11091939
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Disposal Solution for Control of a Giant Landslide and Dammed Lake in Yangtze River, China

Abstract: Although landslide early warning and post-assessment is of great interest for mitigating hazards, emergency disposal solutions for properly handling the landslide and dammed lake within a few hours or days to mitigate flood risk are fundamentally challenging. In this study, we report a general strategy to effectively tackle the dangerous situation created by a giant dammed lake with 770 million cubic meters of water volume and formulate an emergency disposal solution for the 25 million cubic meters of debris, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Their results indicate that flood control for small-and medium-scale rivers in highly urbanized areas should not simply consider tributary flood regimes but, rather, involve both tributary and mainstream flood characters from a whole region perspective. In [14], the authors report emergency disposal solutions for properly handling the landslide and dammed lake within a few hours up to days for mitigating flood risk. They present a general strategy to effectively tackle the dangerous situation created by a giant dammed lake with 770 million m 3 of water volume and formulate an emergency disposal solution for the 25 million m 3 of debris, composed of engineering measures of floodgate excavation and non-engineering measures of reservoirs/hydropower stations operation.…”
Section: Summary Of the Papers In The Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…Their results indicate that flood control for small-and medium-scale rivers in highly urbanized areas should not simply consider tributary flood regimes but, rather, involve both tributary and mainstream flood characters from a whole region perspective. In [14], the authors report emergency disposal solutions for properly handling the landslide and dammed lake within a few hours up to days for mitigating flood risk. They present a general strategy to effectively tackle the dangerous situation created by a giant dammed lake with 770 million m 3 of water volume and formulate an emergency disposal solution for the 25 million m 3 of debris, composed of engineering measures of floodgate excavation and non-engineering measures of reservoirs/hydropower stations operation.…”
Section: Summary Of the Papers In The Special Issuementioning
confidence: 99%
“…Multidisciplinary research and advanced methodologies in hydrological forecasts, especially in extreme floods and droughts, are widely implemented for water planning and management, which ultimately lead to improved optimum water resources management and effective control under a changing environment. Among them, artificial intelligence (AI) techniques are efficient tools for extracting the key information from complex highly dimensional input-output patterns and are widely used to tackle various hydrological problems such as flood forecasts discussed in this Special Issue [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Over the last decades, many studies have demonstrated that artificial intelligence (AI) techniques, such as machine learning (ML) methods, can produce flood forecasts in a few hours [15][16][17][18][19] while extending to seasonal forecasts many months in advance for larger river basins [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%